The emergence of DNAM-1 as the facilitator of NK cell-mediated killing in ovarian cancer - Rachel Pounds; Rachel Pounds; Wayne Croft; Hayden Pearce; Tasnia Hossain; Kavita Singh; Janos Balega; David N. Jeevan; Sudha Sundar; Sudha Sundar; Sean Kehoe; Jason Yap; et al. (Frontiers in Immunology, 2025)
IntroductionOvarian cancer (OC) is the sixth most common malignancy in women and the poor 5-year survival emphasises the need for novel therapies. NK cells play an important role in the control of malignant disease but the nature of tumour-infiltrating and peripheral NK cells in OC remains unclear.MethodsUsing flow cytometric analysis, we studied the phenotype and function of NK cells in blood, primary tumour and metastatic tissue in 80 women with OC. The cell type contexture of metastatic OC tissue was explored utilising scRNAseq analysis, with a focus on portraying an immunogenic tumour microenvironment and determining the characteristics of a dysfunctional NK cell population.ResultsThe proportion of peripheral NK cells was markedly elevated with a highly activated profile and increased cytotoxicity. In contrast, NK cell numbers in primary tumour and metastasis were substantially reduced, with downregulation of activatory receptors together with elevated PD-1 expression. scRNA-Seq identified 5 NK cell subpopulations along with increased exhausted and immature NK cells within tumour tissue compared to normal tissue. These features were attenuated following chemotherapy where higher levels of activated and cytotoxic NK cells associated with improved disease-free survival. Correlation of NK cell phenotype with clinical outcomes revealed high levels of DNAM-1 expression on tissue-localised and peripheral NK cells to be associated with reduced survival. Expression of PVR, the DNAM-1 ligand, was significantly increased on tumours and DNAM-1 mediated NK cell lysis of primary tumour tissue was observed in vitro.DiscussionThese findings reveal profound modulation of the tumour tissue and systemic profile of NK cells which likely contributes to the high rates of local progression and metastasis seen with OC. Immunotherapeutic approaches that overcome local immune suppression and enhance DNAM-1-targeted lysis of OC offer the potential to improve disease control.